Proceedings of the 2013 ACM International Conference on Interactive Tabletops and Surfaces 2013
DOI: 10.1145/2512349.2512811
|View full text |Cite
|
Sign up to set email alerts
|

The effect of egocentric body movements on users' navigation performance and spatial memory in zoomable user interfaces

Abstract: We present two experiments examining the impact of navigation techniques on users' navigation performance and spatial memory in a zoomable user interface (ZUI). The first experiment with 24 participants compared the effect of egocentric body movements with traditional multi-touch navigation. The results indicate a 47% decrease in path lengths and a 34% decrease in task time in favor of egocentric navigation, but no significant effect on users' spatial memory immediately after a navigation task. However, an add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 29 publications
0
34
1
Order By: Relevance
“…Scholars in HCI increasingly are turning their attention to interactive maps (e.g. Hecht et al, 2013;Rädle, Jetter, Butscher, & Reiterer, 2013;Schöning et al, 2008), again pointing to an increased mutual influence as maps become interactive and move online or to mobile devices.…”
Section: Human-computer Interaction and Usability Engineeringmentioning
confidence: 99%
“…Scholars in HCI increasingly are turning their attention to interactive maps (e.g. Hecht et al, 2013;Rädle, Jetter, Butscher, & Reiterer, 2013;Schöning et al, 2008), again pointing to an increased mutual influence as maps become interactive and move online or to mobile devices.…”
Section: Human-computer Interaction and Usability Engineeringmentioning
confidence: 99%
“…Although body panning did not result in an increased navigation performance, participants performed better with regard to object location memory. Similarly, Rädle et al [22] investigated the effect of egocentric movements in peephole navigation of zoomable peephole interfaces, concluding with a positive effect of egocentric body movements on spatial memory.…”
Section: Influence Of Input Modalitymentioning
confidence: 99%
“…We used a well-established and validated task [11,13,15,16,17,22] consisting of a navigation phase and a subsequent object location memory phase (see the video in supplemental materials). Using one of the input modalities, a canvas could be navigated using panning operations.…”
Section: Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012 Rädle et al [11] compared egocentric navigation with traditional touch navigation in terms of navigation performance, spatial memory, and subjective workload. Their study revealed an effect on navigation performance and long term spatial memory in favor of egocentric navigation.…”
Section: Research On Cognitive Aspectsmentioning
confidence: 99%